Katalog Rencana - Agung, Anak Agung Gde (Journal of Regional and City Planning, 2003)
The development of information technology offers various capabilities for us to exchange information more effectively and cheaper. This article discusses the development of planning catalog, i.e. a site in Internet where we can get access to various sources of planning information which are spread geographically and institutionally .The application of a catalog model that has succeeded in spreading the geographical information has become an alternative for information exchange among the governmental agencies and between the government and the general public.